2012
DOI: 10.1111/j.1460-9568.2011.07941.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between unconscious motor response facilitation and conflict in medial frontal areas

Abstract: Masked prime tasks have shown that sensory information that has not been consciously perceived can nevertheless modulate behavior. The neuronal correlates of behavioral manifestations of visuomotor priming remain debated, particularly with respect to the distribution and direction (i.e. increase or decrease) of activity changes in medial frontal areas. Here, we predicted that these discrepant results could be accounted for by two automatic and unconscious processes embedded in this task: response conflict and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 53 publications
2
36
1
Order By: Relevance
“…A positive correlation between the conflict-induced medial-frontal theta power and the magnitude of participant's slowdown further suggested that theta oscillations in the mPFC not only participate in the monitoring of attended conflicting events, but also may regulate inappropriate responses triggered by unattended conflicting information presented in the periphery. These findings cast doubts on traditional views which have stressed that high-level control functions of the mPFC, such as conflict-monitoring, rely exclusively on top-down and conscious processes (Dehaene et al, 2003;Jack and Shallice, 2001;Posner, 1994;Posner and DiGirolamo, 1998;Ridderinkhof et al, 2004) and give support to new evidence suggesting that mPFC control functions can potentially operate without conscious awareness (D'Ostillio and Garraux, 2012;Sumner et al, 2007;van Gaal et al, 2008;van Gaal et al, 2010b;van Gaal et al, 2011;Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A positive correlation between the conflict-induced medial-frontal theta power and the magnitude of participant's slowdown further suggested that theta oscillations in the mPFC not only participate in the monitoring of attended conflicting events, but also may regulate inappropriate responses triggered by unattended conflicting information presented in the periphery. These findings cast doubts on traditional views which have stressed that high-level control functions of the mPFC, such as conflict-monitoring, rely exclusively on top-down and conscious processes (Dehaene et al, 2003;Jack and Shallice, 2001;Posner, 1994;Posner and DiGirolamo, 1998;Ridderinkhof et al, 2004) and give support to new evidence suggesting that mPFC control functions can potentially operate without conscious awareness (D'Ostillio and Garraux, 2012;Sumner et al, 2007;van Gaal et al, 2008;van Gaal et al, 2010b;van Gaal et al, 2011;Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 58%
“…Consequently, it is possible that the mPFC responds to all kinds of non-conscious conflicting and errorprone events in a graded manner depending on the robustness of the representation of the experienced conflict (Horga and Maia, 2012). In agreement with this idea, previous studies using subliminal-priming paradigms have shown that the mPFC is sensitive to response conflict and related compensatory control processes even in conditions of reduced perceptual awareness (D'Ostillio and Garraux, 2012;Sumner et al, 2007;van Gaal et al, 2010b) and is responsive to unaware error responses (Hester et al, 2005;Nieuwenhuis et al, 2001).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The invisible stop signal triggered a wave of brain activity that could be tracked by electroencephalographic recordings (EEG) and functional magnetic resonance imaging deep into the 'executive networks' of the frontal cortex that are crucial for controlling our actions [1,[4][5][6]. Similarly, in recent years it has been shown that frontal executive networks of our brain can unconsciously register the occurrence of response errors [7][8][9], conflicting response alternatives [10][11][12] and competing task sets [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Under this account, unconscious attention and prediction may operate synergistically to facilitate stimulus processing. Importantly, it has been suggested that prefrontal cortical regions, particularly the dlPFC, are functionally implicated in top-down prediction and unconscious processing (Brown et al, 2008;D'Ostilio & Garraux, 2012;Walsh & Phillips, 2009). In this case, unconscious attention and prediction might interact in the dlPFC.…”
Section: Introductionmentioning
confidence: 96%